Long-Term International Capital Movements and Technology : A Review - Zebregs, Harm (IMF Working Papers; Working Paper ;, 1999)
This paper reviews the theoretical literature on the question of how long-term international capital movements depend on the international distribution of technology. It focuses on long-term investment flows, as these are more affected by international differences in technologies than short-term financial flows. International capital movements are investigated in the context of various technology specifications, ranging from models with only one common technology to those with multiple and endogenous technologies. The paper demonstrates that the theoretical specification of technology is crucial to the prediction of the size and direction of international capital movements.